A benchmarking scoping review of research output from hospital pharmacy departments in Australia. (23rd May 2022) - Penm, Jonathan; Narayan, Sujita; Alffenaar, Jan‐Willem; Johnson, Jacinta L.; Mirkov, Sanja; Page, Amy T.; Pont, Lisa G.; Patanwala, Asad E.
Abstract: Aim: To benchmark annual research output from hospital pharmacy departments in Australian principal referral hospitals. Data sources: Embase, Medline, and Scopus. Study selection: All 29 principal referral hospitals listed by the Australian Institute of Health and Welfare were searched using the institution field from 2018–2020. Articles were included if an author was affiliated with a hospital pharmacy department. Conference abstracts, letters, narrative reviews, opinions, commentaries, or editorials were excluded. Results: A total of 261 research articles were identified from 27 principal referral hospital pharmacy departments from 2018–2020. Median research output over 3 years was five (interquartile range, 3–9) articles. In terms of annual research, hospital pharmacy departments in the 50th and 90th percentile for total publication output published two and ten original research articles every year, respectively. Overall, 56% ( n = 145) of the published studies were observational, 35% (n  = 90) had a first author with a pharmacy department affiliation, 97% ( n = 252) had at least one author with a university affiliation, and in 5% ( n  = 12) of the articles there was more than one hospital pharmacy department affiliation. Conclusion: On average, hospital pharmacy departments in Australian principal referral hospitals publish two original research articles every year. Nearly all of these articles are published in collaborations with universities.